Global elective breast- and colorectal cancer surgery performance backlogs, attributable mortality and implemented health system responses during the COVID-19 pandemic: A scoping review. - Sonia Haribhai; Komal Bhatia; Maryam Shahmanesh (PLOS Global Public Health)
Globally, 28.4 million non-emergent ('elective') surgical procedures have been deferred during the COVID-19 pandemic. This study evaluated the impact of the COVID-19 pandemic on elective breast- or colorectal cancer (CRC) procedure backlogs and attributable mortality, globally. Further, we evaluated the interaction between procedure deferrals and health systems, internationally. Relevant articles from any country, published between December 2019-24 November 2022, were identified through searches of online databases (MEDLINE, EMBASE) and by examining the reference lists of retrieved articles. We organised health system-related findings thematically per the Structures-Processes-Outcomes conceptual model by Donabedian (1966). Of 337 identified articles, we included 50. Eleven (22.0%) were reviews. The majority of included studies originated from high-income countries (n = 38, 76.0%). An ecological, modelling study elucidated that global 12-week procedure cancellation rates ranged from 68.3%-73%; Europe and Central Asia accounted for the majority of cancellations (n = 8,430,348) and sub-Saharan Africa contributed the least (n = 520,459). The percentage reduction in global, institutional elective breast cancer surgery activity ranged from 5.68%-16.5%. For CRC, this ranged from 0%-70.9%. Significant evidence is presented on how insufficient pandemic preparedness necessitated procedure deferrals, internationally. We also outlined ancillary determinants of delayed surgery (e.g., patient-specific factors). The following global health system response themes are presented: Structural changes (i.e., hospital re-organisation), Process-related changes (i.e., adapted healthcare provision) and the utilisation of Outcomes (i.e., SARS-CoV-2 infection incidence among patients or healthcare personnel, postoperative pulmonary complication incidence, hospital readmission, length of hospital stay and tumour staging) as indicators of health system response efficacy. Evidence on procedure backlogs and attributable mortality was limited, partly due to insufficient, real-time surveillance of cancer outcomes, internationally. Elective surgery activity has decreased and cancer services have adapted rapidly, worldwide. Further research is needed to understand the impact of COVID-19 on cancer mortality and the efficacy of health system mitigation measures, globally.